Altered Expression of Cellular Bcl-2 in the Progression of Hamster Cholangiocarcinogenesis - Byung-suk Jeon; Byung-IL Yoon (The Scientific World Journal)
Bcl-2 is an intracytoplasmic and membrane-associated apoptosis suppressor, and its overexpression is closely associated with survival of malignant tumors, in particular their aggressive behavior and poor prognosis. The role of Bcl-2 is, however, still controversial in cholangiocarcinogenesis because of the discrepancies in the expression of the protein. In the present study, alteration in the expression of Bcl-2 in cholangiocarcinogenesis was investigated by studying the immunoreactivities of this protein in normal, hyperplastic bile ducts with or without dysplastic changes, and neoplastic bile duct cells from a hamster cholangiocarcinoma (ChC) model. Cytoplasmic staining, which reflects high-Bcl-2 immunoreactivity, was negative to very weak in normal and hyperplastic bile ducts without dysplastic changes, while hyperplastic bile ducts with dysplasia indicated heterogeneously strong expression. On the other hand, most of the neoplastic cells of invasive cholangiocarcinomas were negative to weak as much as the level of normal bile ducts. The results suggest that the antiapoptotic factor Bcl-2 plays a limited role in the survival of highly proliferative, potentially dysplastic bile duct cells. However, the role of Bcl-2 in biliary cancer cells was not significant.